ANALISIS PARTISIPASI ANGGOTA YANG AKTIF PADA UNIT TOKO KOPERASI PEGAWAI NEGERI UNIVERSITAS TANJUNGPURA PONTIANAK - Imj, Rosilia; Parijo, Parijo; BU, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research started from the researcher interest on the buying and selling activities at KPN Untan less developed shop units and the number of members who actively participate in the meaning of shopping for basic needs is relatively small compared to the number of members registered in KPN Untan. Whereas at the beginning of the establishment of the unit store KPN Untan was a fairly developed shop units. The general problem in this research was